Impact of sodium metabisulfite on the structural, hematological, and enzyme dynamics in liver and spleen of Wistar rats - Nathaniel Amedu; Habeebullahi Abdur-Rahman (Journal of Research in Applied and Basic Medical Sciences)
Background & Aims: Sodium metabisulfite (SMB) is widely used in the pharmaceutical and food industries for its antioxidant and antimicrobial properties; however, its potential to generate toxic oxidants raises concerns. This study aimed to investigate the structural alterations, blood parameters, and enzyme dynamics associated with SMB exposure in the liver and spleen of Wistar rats. Materials & Methods: Twenty-four juvenile Wistar rats were randomly divided into four groups consisting of six rats each: Group 1 (control) received 0.5mL normal saline; Group 2 was administered 100 mg/kg SMB; Group 3 received 300 mg/kg SMB; and Group 4 was given 500 mg/kg SMB. The administration was conducted orally over a period of 28 days, after which the rats were euthanized for tissue collection. Blood samples were obtained to analyze red blood cell (RBC) count, hemoglobin (Hb) count, platelets (PLT) count, and white blood cell (WBC) count, while liver and spleen tissue samples were collected for alkaline phosphatase (ALP), alanine aminotransferase (ALT), and aspartate aminotransaminase (AST) assays, along with histopathological examination using haematoxylin and eosin staining. Results: In rats given SMB at 500mg/kg, RBC levels were significantly lower compared to the control and SMB 100 mg/kg groups. PLTs were significantly reduced in the SMB 300 mg/kg and 500mg/kg groups. No significant differences were observed in WBC and Hb levels. ALP, alanine aminotransferase, and aspartate aminotransferase levels were significantly higher in rats given SMB at varying doses, with higher doses causing greater elevation. Liver histology revealed hepatocellular necrosis at 500 mg/kg, while spleen histology showed disrupted architecture at the same dose. Conclusion: The study highlights significant hematological and hepatic effects of varying doses of SMB in rats, emphasizing potential toxicity and necessitating further safety assessments.